A prospective comparative study of detection of colonic polyposis by magnetic resonance colonography versus conventional colonoscopy - Ramana, Kada Venkata; Kumar, Tripuraneni Rajesh (International Surgery Journal, 2019)
Background: Colorectal cancer mostly arises from adenomatous polyp and the transition time to convert into carcinoma is around ten years. As the progress to adenocarcinoma is a slow process so, early detection and endoscope resection is claimed to be effective in decreasing incidence and mortality by colorectal cancer. MR colonography is a non-invasive method for evaluating entire colon. It can detect precancerous lesion, cancer and staging. It is non-invasive tool for screening. Acceptability of the patient is better for MR colonography. Methods: Present study is a prospective comparative evaluation of magnetic resonance colonography verses colonoscopy conducted in the Department of Radiology, Konaseema Institute of Medical Science, and other establishments from August 2015 to January 2018. The sample size was calculated to be 112. Specificity, sensitivity and predictive value were calculated by medical statistical software. Results: For all size of tumours, sensitivity was 85.71%, specificity was 92.85%, positive predictive value was 92.30%, negative predictive value was 86.66% and accuracy was 94.34%. The positive predictive value was 90.00% negative predictive value was 92.68% and accuracy was 92.16%. For 1 mm to 4 mm size of polyp the sensitive was 28.57%, specificity was 92.31%, positive predictive value was 66.67%, negative predictive value was 70.59% and accuracy was 70%. Conclusions: In present study we have found that there was male predominance in patient and gastrointestinal bleeding was common clinical presentation. We have also observed that all size of poly MR colonography as having sensitivity and specificity around 90% but MR colonography is highly sensitive and specific for polyp size above 8mm but it is less sensitive for size below 4 mm.